2015
DOI: 10.4187/respcare.04004
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Responses, Spirometry, and Quality of Life in Subjects With Bronchiectasis Exacerbations

Abstract: BACKGROUND: Bronchiectasis exacerbations are critical events characterized by worsened symptoms and signs (ie, cough frequency, sputum volume, malaise). Objectives: Our goal was to examine variations in airway and systemic inflammation, spirometry, and quality of life during steady state, bronchiectasis exacerbations, and convalescence (1 week following a 2-week antibiotic treatment) to determine whether potentially pathogenic microorganisms, including Pseudomonas aeruginosa, were associated with poorer condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 36 publications
0
19
0
2
Order By: Relevance
“…Bacterial load in non-CF bronchiectasis has been correlated with increases in airway (NE, IL-8, IL-1β and TNF-α) and systemic (ICAM-1, E-selectin) derived inflammatory markers, phenomena confirmed in vitro using bronchial epithelial cell lines treated with sputum from bronchiectasis patients [103,104]. Exacerbations of both CF and non-CF bronchiectasis increases inflammation irrespective of bacterial, viral or fungal causation [43,105,106]. Interestingly, sTREM-1 a novel inflammatory marker described in a variety of pulmonary disease states including COPD, has also been identified in children with both CF-and HIV-related bronchiectasis although concentrations in the latter setting are highest.…”
Section: Immunology and Inflammationmentioning
confidence: 88%
“…Bacterial load in non-CF bronchiectasis has been correlated with increases in airway (NE, IL-8, IL-1β and TNF-α) and systemic (ICAM-1, E-selectin) derived inflammatory markers, phenomena confirmed in vitro using bronchial epithelial cell lines treated with sputum from bronchiectasis patients [103,104]. Exacerbations of both CF and non-CF bronchiectasis increases inflammation irrespective of bacterial, viral or fungal causation [43,105,106]. Interestingly, sTREM-1 a novel inflammatory marker described in a variety of pulmonary disease states including COPD, has also been identified in children with both CF-and HIV-related bronchiectasis although concentrations in the latter setting are highest.…”
Section: Immunology and Inflammationmentioning
confidence: 88%
“…En esta investigación se encontró una mejora, estadísticamente significativa, en los valores de la CPT, VR, y VR/CPT luego de la aplicación de broncodilatadores. Esto concuerda con lo observado por Guan Wei-Jie et al [8] donde el 34% de su población respondieron positivamente a los broncodilatadores. Esto se explicaría porque las bronquiectasias se comportan como una enfermedad crónica y progresiva que comprende un grado de obstrucción crónica del flujo aéreo [9,10] , lo que demostraría cierto grado de reversibilidad de dicha obstrucción bronquial, quizá parecido a lo que ocurre en la EPOC.…”
Section: Discussionunclassified
“…It is important to note that spirometry may not significantly differ between the stable and exacerbation states 35. Although one study showed a statistically significant decline of both FEV1 and FVC by 3% ( P ≤.01) between the stable and exacerbation states, this is unlikely to be clinically significant 59. Spirometry should be performed at least annually in patients with bronchiectasis to detect progression of the disease 1.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…35 Although one study showed a statistically significant decline of both FEV1 and FVC by 3% (P≤.01) between the stable and exacerbation states, this is unlikely to be clinically significant. 59 Spirometry should be performed at least annually in patients with bronchiectasis to detect progression of the disease. 1 Pulmonary function testing may help detect and determine the severity of other underlying conditions such as interstitial lung disease, asthma and pulmonary hypertension.…”
Section: Pulmonary Function Testingmentioning
confidence: 99%